FACTORS RELATED TO LOW BACK PAIN (COMPLAINTS OF LOW BACK PAIN) IN JAMBI-BANGKO TRAVEL CAR DRIVERS IN 2022 - Syarah Rahmadina; T. Samsul Hilal; Eti Kurniawati (Sekolah Tinggi Pariwisata Mataram, 2023)
LBP is a form of musculoskeletal disorder caused by poor body activity. Travel car drivers are one of the professions that have the risk of experiencing LBP. Risk factors for LBP in travel car drivers include length of service, age, anthropometry. Travel car drivers who work with the wrong body position will cause LBP which is affected by the physical condition of the car driver. This study is a quantitative research with a cross-sectional approach that aims to find out the factors related to low back pain (LBP) complaints. The population in this study was all 48 travel car drivers majoring in Jambi-Bangko. The total sample was 48 respondents, the instrument used was a questionnaire sheet and was carried out by filling out a questionnaire, measuring height and weight. The data were analyzed univariately and bivariately using the chi-square test. The results of the analysis showed that there was a relationship between the variable length of service and Low Back Pain (P-value = 0.000), there was no relationship between age and Low Back Pain (P-value = 0.149), there was a relationship between anthropometry and Low Back Pain (P-value = 0.023). It is hoped that travel car drivers can stretch or relax during rest periods, have an ideal weight, and drink more water to replace body fluids.